2019
DOI: 10.3390/plants8080250
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Yield and Seed Composition Changes in Response to Increasing Atmospheric CO2 Concentration in Short-Season Canada

Abstract: From 1993, we have conducted trials with the same set of old to newer soybean cultivars to determine the impact of plant breeding on seed yield, physiological and agronomic characteristics, and seed composition. Since 1993, global atmospheric [CO2] increased by 47 ppm. The objective of our current analysis with this data set was to determine if there were changes in soybean seed yield, quality or phenology attributable to elevated atmospheric CO2 concentration (eCO2), temperature or precipitation. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In line with previous work, we do not consider the effect of an increase in atmospheric CO2 concentration on soybean yields because this effect is still very uncertain due to many complex interaction mechanisms, and is still widely discussed in the research community [63][64][65][66][67][68] . However, if an increase in atmospheric CO2 concentration positively affects soybean yield as suggested by the most up-to-date quantitative synthesis of available experimental and modeling studies (which reports an estimated global average yield increase of soybean of +11% for an increase in atmospheric CO2 concentration of +100ppm) 69 , it further supports our findings that large opportunities exist to improve Europe soybean self-sufficiency under climate change.…”
Section: Potential Effects Of Some Factors Not Included In the Modelmentioning
confidence: 96%
“…In line with previous work, we do not consider the effect of an increase in atmospheric CO2 concentration on soybean yields because this effect is still very uncertain due to many complex interaction mechanisms, and is still widely discussed in the research community [63][64][65][66][67][68] . However, if an increase in atmospheric CO2 concentration positively affects soybean yield as suggested by the most up-to-date quantitative synthesis of available experimental and modeling studies (which reports an estimated global average yield increase of soybean of +11% for an increase in atmospheric CO2 concentration of +100ppm) 69 , it further supports our findings that large opportunities exist to improve Europe soybean self-sufficiency under climate change.…”
Section: Potential Effects Of Some Factors Not Included In the Modelmentioning
confidence: 96%
“…Nighttime temperatures have to exceed 85 • F (approximately 30 • C) before any noticeable reduction in soybean yield is experienced (Farm Progress 2022). Cober and Morrison (2019) found that soybean seed yield was increased significantly by elevated atmospheric CO 2 concentration, higher precipitation and higher minimum temperatures during flowering and podding, although yield decreased with higher minimum temperatures during vegetative growth and seed filling. Given that the respiration rates at 26 and 29 • C were doubled when compared to 20…”
Section: Climate Indicators For Soybeansmentioning
confidence: 98%
“…and while this experiment was not designed to investigate drought stress and soybean protein, it is noteworthy that the irrigated field had higher protein than the dryland field and was the site with the second highest mean protein in this study (Table 4). In our previous work at Ottawa, precipitation during early reproductive growth (flowering and pod development) was the most important environmental factor for seed protein content (Cober and Morrison 2019). Current and newly developing irrigated land in Western Canada may be exploited to produce higher-protein soybeans in the future.…”
Section: Seed Protein Contentmentioning
confidence: 99%
“…While Rotundo et al (2016) found geographical differences for soybean seed protein, year-to-year weather variations also played an important role in soybean seed protein. In examining parameters affecting seed protein in short-season soybeans at Ottawa, precipitation during early reproductive growth (flowering and pod development) was the most important environmental factor for seed protein content, with an increase of 0.17 g kg −1 seed protein for every mm of precipitation (Cober and Morrison 2019). A meta-analysis of factors influencing soybean seed protein indicated that drought stress increased seed protein percentage through less dilution of the protein and not through an increase in protein synthesis (Rotundo and Westgate 2009).…”
Section: Introductionmentioning
confidence: 99%